Student Perception towards Application Performance for Online Learning - Lilis Endang Wijayanti; Ratna Listiana Dewanti; Fran Sayekti (Dinasti International Journal of Management Science, 2023)
This study analyzes students' perceptions of the applications used in e-learning. The study is based onthe pandemic situation which caused major changes in learning. During the pandemic, almost allclasses are conducted online. One of the online meeting media that is widely used is the Zoomapplication. The study will analyze students' perceptions of the performance of applications used foronline learning. The analysis will be based on the Technology Acceptance Model (TAM). TAMhighlights that acceptance of the information system is influenced by perceived usefulness (POU) andperceived ease of use (PEU). This study will adopt the independent variables, namely POU and PEUand analyze their influence on the performance of online learning applications. The study wasconducted in Yogyakarta. Data was obtained by distributing questionnaires to students who weretaking online classes. Data analysis used multiple regression. The results of the analysis show thatPEU and POU affect the performance of online learning applications.Keywords: Online learning, online learning application, Technology Acceptance Model.